THE COMPARATIVE STUDY OF WRITING AND LISTENING ANXIETY OF EFL UNIVERSITY STUDENTS - DARMAWATI DARMAWATI; EKA PALUPI UTAMI (JURNAL ILMIAH SIMANTEK, 2023)
This research is related to the study of writing and listening anxiety to EFL students’ on seventh semester in Muhammadiyah University of North Sumatra using the theory of Cheng for writing anxiety and Kim for listening anxiety. The aim of this research is to identify the factors that impact writing and listening anxiety and then compare anxiety levels among EFL students. This research used quantitative research. From a total of 112 students, researcher used random sampling to take 30 samples using Sugiono’s theory. A questionnaire has been the data collection instrument used by researcher. The writing and listening anxiety questionnaire has twenty items. This research used SPSS 22 to analyze the data with descriptive statistic and paired sample test. The Writing Anxiety and Listening Anxiety subscales had a balanced score, based on the data. That is, the research participants experienced all of the factors stated in each questionnaire. The majority of students were therefore anxious when writing rather than listening to English. Based on the data, the average student who had writing anxiety was 3.2333, and the average student who experienced listening anxiety was 2.4767. Writing anxiety affects up to 16 out of each 30 students, whereas listening anxiety affects up to 3 out of each 30 students. This is due to students' lack of confidence in expressing their ideas and their lack of understanding about good and correct language structures